Grado de eutrofización del humedal La Segua - Vera Rodríguez, Juan Patricio (2021)
The objective of this research was to evaluate the degree of eutrophication of the La Segua wetland. For this, the current situation of aquaculture activities in the wetland was described, where the study area was recognized, detailing the main access routes and the water inputs of the site, in the same way a survey applied to the workers was carried out; In addition, the trophic degree of the water was determined during the months of October, November and December 2020, and January 2021. The physicochemical parameters of chlorophyll, total phosphorus and turbidity were analyzed, through the use of methodologies proposed by the trophic state index Carlson's modified by Toledo, which had a eutrophic classification with a value of 91.09 on its scale; and hypertrophic for the Lamparelli modified trophic state index with a value of 76.17. Finally, an analysis of the results obtained was carried out by means of which it was found that there is no significant difference in the values derived from the months that the investigation lasted, Likewise, by means of isoline graphs, it was found that, adjacent to the water discharge areas used by the shrimp farms, the eutrophication levels were higher in relation to the central area of the wetland.